Validity of Active Motor Card 3 Locomotives Aged 10-12 Years for Elementary School Students in Malang City - Ramadhan Adrias Hariadi; Nurrul Riyad Fadhli (Journal of Physical and Outdoor Education, 2025)
This study aims to determine the level of validity of Active Motor Card 3 in improving the motor skills of elementary school children in Malang City, and to measure the effectiveness of Active Motor Card 3 in providing practical recommendations for educators. The research design used a non-experimental one. This design includes expert tests on instrument evaluation and physical education experts. The population of this study were students of SDN Sumbersari 3 Malang City with details of the age group 10-12 years or grades 4, 5, and 6. The sampling technique used purposive sampling. Data collection techniques used non-test and test techniques. The non-test technique used a Likert scale to analyze the instrument and the test used the AMC-3 and TGMD-3 tests. This data collection was carried out from August to September 2024. The results of the instrument expert validation produced an average of 95% (valid). Based on the average r count results on AMC-3 of 0.917 and the correlation between AMC-3 and TGMD-3 produced an average r count of 0.532 with r table of 0.2199 significance of 0.05. So it can be concluded that the AMC-3 (locomotor) instrument is valid and can be a recommendation for motor assessment of children aged 10-12 years.